Uji daya hambat ekstrak daun mengkudu (Morinda citrifolia L.) terhadap pertumbuhan Candida albicans secara in vitro - Simatupang, Olivia C.; Abidjulu, Jemmy; Siagian, Krista V. (e-GiGi, 2017)
Abstract: Candida albicans is a normal flora of the mouth, respiratory tract, gastrointestinal tract and the female genital but it becomes pathogen if there is a predisposing factor. Approximately 85-95% of oral candida infections are caused by C. albicans that is usually attached to the labial mucosa, buccal mucosa, the dorsal parts of the tongue and palate. Noni (Morinda citrifolia L.) is already known as a medical plant; one of it parts that has a medicinal effect is the leaf that contains anthraquinon as an antifungal. This study was aimed to determine the effect of noni leaf extract to the growth of C. albicans. This was a true experimental in vitro study with the post test only group design. The Kirby-Bauer method with filter paper was used to evaluate the sensitivity of C. albicans to mengkudu leaf extract. Leaves samples were extracted by using maceration process with ethanol 96%. C. albicans obtained from the pure stock of Laboratory of Microbiology Pharmacy Faculty of Math and Science, University of Sam Ratulangi. The results showed that the inhibition zone diameter of noni leaf extract on the growth of C. albicans was 16 mm (strong inhibition category). Conclusion: Noni leaf extract (Morinda citrifolia L.) had an inhibitory effect on Candida albicans.Keywords: Mengkudu leaf (Morinda citrifolia L.), Candida albicans, inhibition zoneÂ Abstrak: Candida albicans merupakan anggota flora normal rongga mulut, saluran pernafasan, saluran pencernaan, dan genital wanita namun dapat menjadi patogen jika terdapat faktor predisposisi. Sekitar 85-95% infeksi kandidiasis oral disebabkan oleh C albicans yang biasanya melekat pada mukosa labial, mukosa bukal, dorsum lidah dan palatum. Tanaman mengkudu (Morinda citrifolia L.) telah dikenal sebagai tumbuhan obat. Salah satu bagian tanaman mengkudu yang memiliki efek obat ialah daunnya karena adanya kandungan antrakuinon yang bersifat antijamur. Penelitian ini bertujuan untuk mengetahui efek ekstrak daun mengkudu terhadap pertumbuhan C. albicans. Jenis penelitian ini ialah eksperimental laboratorik secara in vitro dengan post test only group design. Pengujian menggunakan metode Kirby-Bauer berbahan kertas saring. Sampel daun diekstraksi dengan proses maserasi menggunakan etanol 96%. Jamur C. albicans diambil dari stok biakan jamur murni Laboratorium Farmasi FMIPA Universitas Sam Ratulangi Manado. Hasil penelitian mendapatkan diameter zona hambat ekstrak daun mengkudu terhadap pertumbuhan C. albicans 16 mm yang tergolong kriteria zona hambat kuat. Simpulan: Ekstrak daun mengkudu (Morinda citrifolia L.) mempunyai daya hambat terhadap jamur Candida albicans.Kata kunci: daun mengkudu, Candida albicans, zona hambat